Penggunaan Inventori Sepok Tuah Arahan Diri (STAD) dalam Membantu Siswa SMA Memahami Dirinya - Syarifuddin Dahlan (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2005)
This quasi experimental study is intended to examine the effectiveness of Spok Tuah Arahan Diri (STAD) in helping clients understand their personalities. A pretest and post test design was employed to 48 senior high school students. The results of t-test show that STAD effectively helped improve self understanding. It is then suggested that the STAD inventory be used in guidance and counselling programs at schools.